Corporate Disclosure, Compliance and Consequences: Evidence from Russia - Suman Banerjee; Saul Estrin; Sarmistha Pal (Institute of Labor Economics (IZA), 2022)
Does the introduction of corporate transparency and disclosure rules in emerging economies affect compliance, and therefore earnings quality and firm performance? We explore these questions for an important emerging economy, Russia, using a natural experiment, the 2002 introduction of Russian corporate governance code. We exploit the exogenous variation in voluntary disclosure and find a significant increase in corporate disclosure among the domestic Russian firms over the period 2003-07 when firms gradually adopted some but not all disclosure rules. The immediate effect of the introduction was a drop in reported earnings. Market valuation, however, only improved for domestic firms after 2007, when all domestic firms had complied. However, cross-listed firms, which were already satisfying international standards, remained largely unaffected. Though average compliance by domestic firms was only 53%, average firm value of treated domestic firms, relative to cross-listed ones, went up by about 10%. Results are robust, confirm external validity and offer important policy implications for other emerging/transition economies.
Keywords: G3; K29; O38; 330; increased disclosure; processing cost of information; market valuation; reported earnings; cost of capital; domestic vs. cross-listed firms; 2002 Russian Corporate Governance Code; difference-in-difference model; Russia